2003
DOI: 10.1128/jvi.77.23.12430-12440.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sequential Viral Escape Mutants Associated with Altered T-Cell Responses in a Human Immunodeficiency Virus Type 1-Infected Individual

Abstract: Control of viremia in natural human immunodeficiency virus type 1 (HIV-1) infection in humans isassociated with a virus-specific T-cell response. However, still much is unknown with regard to the extent of CD8 ؉ cytotoxic T-lymphocyte (CTL) responses required to successfully control HIV-1 infection and to what extent CTL epitope escape can account for rises in viral load and ultimate progression to disease. In this study, we chose to monitor through full-length genome sequence of replication-competent biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 55 publications
2
60
0
Order By: Relevance
“…In a recent study, high-or moderate-avidity CTLm targeting Revepitopes have been found in nonprogressor EIAV-infected animals, suggesting that CTL response against a non-variable viral peptide may be a critical element for virus control [114]. Interestingly, as previously described during HIV and SIV infections in primates [39,45,69,119], viral evolution in EIAV-gag and env genes led to CTL escape [114]. EIAV-neutralizing antibodies that are able to block the infecting strain usually emerge only after two or three months post infection [5,51,61,75,123] suggesting that they are not responsible for the termination of the acute episode.…”
Section: Immune Control Of Eiav Infection and Replicationmentioning
confidence: 53%
“…In a recent study, high-or moderate-avidity CTLm targeting Revepitopes have been found in nonprogressor EIAV-infected animals, suggesting that CTL response against a non-variable viral peptide may be a critical element for virus control [114]. Interestingly, as previously described during HIV and SIV infections in primates [39,45,69,119], viral evolution in EIAV-gag and env genes led to CTL escape [114]. EIAV-neutralizing antibodies that are able to block the infecting strain usually emerge only after two or three months post infection [5,51,61,75,123] suggesting that they are not responsible for the termination of the acute episode.…”
Section: Immune Control Of Eiav Infection and Replicationmentioning
confidence: 53%
“…We studied ex vivo functional cross-recognition of variants of four different HLA-B57-restricted HIV-1 epitopes: KAFSPEVIPMF Gag p24 30 -40 (B57-KAF), TSTLQEQIGW Gag p24 108 -117 (B57-TST), ISPRTLNAW Gag p24 [15][16][17][18][19][20][21][22][23] , (B57-ISP), and QASQEVKNW Gag p24 176 -184 (B57-QAS), responses to which have been reported in HLA-B57 ϩ LTNPs (31-33, 46, 47). Overall, B57-KAF-specific responses were efficient in recognizing alanine-substituted variants, although there was considerable interpatient variability in the patterns of cross-reactivity observed.…”
Section: Functional Cross-recognition Of Alanine-substituted Variantsmentioning
confidence: 99%
“…Escape may be minimized when the CD8 response is focused predominantly on epitopes located in structurally important regions of the virus (where acquisition of amino acid changes is associated with high costs to intrinsic viral fitness) (7,13,14), or where the response is more evenly directed toward multiple HIV-1 epitopes (so that the selective pressure for amino acid change in each individual epitope is reduced) (15,16). Indeed, escape of other persistent viruses from CD8 ϩ T cell recognition is seen where the response is directed toward a limited number of epitopes (17,18) and rapid escape from narrowly directed vaccineinduced CD8 ϩ T cell responses has been reported in SIV/simian HIV macaque models of infection (19 -21).…”
Section: Irus-specific Cd8mentioning
confidence: 99%
“…The number of simultaneously targeted epitopes has been estimated from analyses of sequence data from all or most viral genes, which found escape mutations at zero to five epitopes spreading to fixation simultaneously (Goulder et al 1997;Geels et al 2003;Milicic et al 2005). Since these analyses likely underestimate the number of targeted epitopes, use of the maximum number is justified (Asquith et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The fitness cost of an escape mutation was f ¼ 0.005 day 21 (Asquith et al 2006). The number of epitopes targeted simultaneously has been estimated to range from zero to five, with a median of two (Goulder et al 1997;Geels et al 2003;Milicic et al 2005).…”
Section: Peak Viremiamentioning
confidence: 99%